Brain change trajectories that differentiate the major psychoses. (15th June 2016) - Liberg, Benny; Rahm, Christoffer; Panayiotou, Anita; Pantelis, Christos
Abstract: Background: Bipolar disorder and schizophrenia are highly heritable, often chronic and debilitating psychotic disorders that can be difficult to differentiate clinically. Their brain phenotypes appear to overlap in both cross‐sectional and longitudinal structural neuroimaging studies, with some evidence to suggest areas of differentiation with differing trajectories. The aim of this review was to investigate the notion that longitudinal trajectories of alterations in brain structure could differentiate the two disorders. Design: Narrative review. We searched MEDLINE and Web of Science databases in May 2016 for studies that used structural magnetic resonance imaging to investigate longitudinal between‐group differences in bipolar disorder and schizophrenia. Ten studies met inclusion criteria, namely longitudinal structural magnetic resonance studies comparing bipolar disorder (or affective psychosis) and schizophrenia within the same study. Results: Our review of these studies implicates illness‐specific trajectories of morphological change in total grey matter volume, and in regions of the frontal, temporal and cingulate cortices. The findings in schizophrenia suggest a trajectory involving progressive grey matter loss confined to fronto‐temporal cortical regions. Preliminary findings identify a similar but less severely impacted trajectory in a number of regions in bipolar disorder, however, bipolar disorder is also characterized by differential involvement across cingulate subregions. Conclusion: The small number of available studies must be interpreted with caution but provide initial evidence supporting the notion that bipolar disorder and schizophrenia have differential longitudinal trajectories that are influenced by brain maturation.